Tinjauan Yuridis Penggunaan Prinsip De Minimis Pada Sengketa Desain Industri antara Ventela dengan Vans - Rianda Dirkareshza; Prisca Dwi Maylinda; Muhammad Fathan Aliqa El Mubarok (Al-Azhar Islamic Law Review, 2023)
Industrial design is an applied art where the aesthetics and usability of an item are perfected. Design work is considered intellectual property because it is the product of the designer's thoughts and creativity so the copyright is protected by the government through Law No. 31 of 2000 concerning Industrial Design. This paper will discuss the use of the de minimis principle in the Industrial Design Law as well as the form of violation of Ventela's industrial design against Vans based on the De Minimis principle. This research is a type of normative juridical research, with a statutory approach and a conceptual approach. Based on the discussion that has been carried out in this paper, it is concluded that in the de minimis principle there are known factors that are usually considered by courts in applying the De Minimis doctrine, where these factors consist of the size and type of loss as well as the intention of the perpetrator. Even the industrial design dispute that occurred between Ventela and Vans shoes still has differences and the De Minimis principle can be applied because it fulfills the factors that become the parameters for the application of the De Minimis principle. Thus it is necessary to accommodate the De Minimis principle in the industrial design law as a solution to this problem.